Characterization of Bi2/3Cu3Ti4O12 ceramics synthesized by semi-wet route - Gautam P.; Khare A.; Sharma S.; Singh N.B.; Mandal K.D. (My University, 2025)
Bi2/3Cu3Ti4O12 (BCTO) ceramic was synthesized by the semi-wet route using metal nitrate solutions and solid TiO2 powder in a stoichiometric ratio. Fourier transform infrared (FTIR) study of BCTO precursor powder and calcined ceramic showed the presence of alcoholic functional groups and the stretching band of Ti-O and Cu-O respectively. X-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive x-ray spectroscopy (EDX) were employed to characterize the structure, surface morphology and purity of the sintered BCTO ceramic respectively. X-ray diffraction study confirmed the single phase formation of BCTO ceramic at 1073 K. The average dimension of grains calculated by SEM and AFM was found to be in the range of 0.73±0.2 µm with clear grain boundaries. Magnetic property was investigated over a wide temperature range 2–300 K at a magnetic field of 7 tesla. The Curie temperature was calculated by zero field cooled (MZFC) and field cooled (MFC) magnetization at 100 Oe applied field which was found to be 125 K. The sintered BCTO ceramic shows high dielectric constant (ε'=2.9×104) at 323 K and 100 Hz. © 2017 Chinese Materials Research Society